Family caregiver’s experiences using community mental health services in Malaysia., - Mohamad, M. S,; Sheau, Tsuey Chong; Hoesni, S. M.,; Subhi, N.,; Sarnon, N.,; Nen, S., (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
Many studies of family caregiving have found mixed findings in evaluating the effectiveness of community services in reducing family caregiver stress. In addition, the study also showed that some of the caregiver has limited experience in obtaining care. The purpose of this article was to describe the experience of the use of community mental health services, including benefits and barriers, by family caregivers of schizophrenic patients in Malaysia. Community mental health services included assistance with caregiving and educational as well as emotional support by community mental health professionals. In this qualitative descriptive study, a purposive sample of 24 family caregivers was interviewed. Semi-structured interview technique was used to explore the caregivers' experiences with community mental health services. Transcribed data were analysed using qualitative frameworkanalysis techniques. Results indicated that family caregivers received benefits of personal respite,sense of community, financial and emotional supports as well as gained practical knowledge and believed that their family also benefited from the community services used. Barriers to service use included lack of attention, accessibility issues and concerns over quality. All the findings in this study provide direction for mental health workers in targeting interventions that will meet the caregivers’ needs and desires.